PENGEMBANGAN PENUNTUN PRAKTIKUM KIMIA BERBASIS LINGKUNGAN PADA MATERI ASAM BASA KELAS XI IPA - Susanti, Jumiana; Enawaty, Eny; Melati, Husna Amalya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aimed to produce a chemical practicum guide environment-based acid-base material that is feasible to use and find out the students' response to the guide that was developed. The form of research used is research and development (R & D) which refers to the 4D development model modified to 3D. The subject of this study was an environment-based chemical practicum guide which was piloted in limited trials and extensive trials. Data collection instruments used were feasibility questionnaires and student response questionnaires. The practicum guide is validated by material experts, linguists and graphic experts. The results of the validation of the practicum guide on the feasibility of the content and presentation obtained a percentage of 92.71% and 89.30%, the linguistic feasibility obtained a percentage of 90.47% and the graphic feasibility of 95.37%. The results of the student testing response were limited to 82.6% and in the extensive trial of 83.2%. The results of the data analysis show that the environmental-based chemistry lab guide is very suitable for use in learning.Keywords: practicum guide, environment-based, acid-base material